(untitled) (Research, Society and Development, 2021)
Introduction: Adult latent diabetes (LADA) is a type 1 diabetes mellitus, in which the main cause is the primary failure in the pancreatic insulin production, in an autoimmune way. Methodology: This is a clinical case report of descriptive analysis with contribution of academic works between the years 2001 and 2020. Case description: Female patient, 65 years old, diagnosed with LADA, makes daily use of insulin from intermediate and slow action, as well as oral anti-diabetic drugs, he was admitted to the hospital with severe hypoglycemia (capillary blood glucose of 51mg/dl), reduced state of consciousness, tachycardia, weakness and muscle spasms, as well as a feeling of cramp in the lower limbs. Laboratory tests showed, through the selective electrode method, that serum potassium levels were 2.80 mEq/L (VR: 3.50 and 5.50 mEq/L), constituting hypokalemia. Discussion: Given that insulin is capable of mobilizing potassium into the cell, small changes in serum potassium may imply profound changes in the conduction and excitability of the heart, which may alter cardiac function and rhythm and even cause cardiorespiratory arrest. Conclusion: Under episodes of severe hypoglycemia, which can be corroborated by the indiscriminate use of insulin doses, one of the exacerbations of the episode is electrolyte imbalance, in short, potassium, given the power of insulin to relocate this electrolyte to the intracellular environment, thus decreasing serum levels and exacerbating with hypokalemia.